Should early career sport scientists strive to be generalists or specialists? - McCunn, R. (The Sport and Exercise Scientist, 2019)
The question in the title of this issue`s column is one that all early career practitioners face, whether they realise it or not. Granted, upon leaving university one`s priority may simply be to get a job, any job, within the field of sport science. However, very quickly thereafter we all face numerous forks in the road. Which further certifications, accreditations and experiences should you seek, and to what end?